Praxias Bucofonatorias en el tratamiento de la dislalia en los niños de primer año de Educación Básica - Gómez Anguisaca, Tania Maribel (2022)
The purpose of this research was to identify the incidence of the bucco-phonotary praxias used in the first year of Basic Education in the canton Pujilí, specifically in the Unidad Educativa "Belisario Quevedo" for the treatment of dyslalia in the process of oral language development of the children of this institution, because it was observed that they present problems in language development, which are reflected in not establishing clear communication, since they substitute, alter, add and omit certain sounds such as: r, s, p, d, rr, y, g, l, diminishing the capacity to emit words, phrases, sentences, rhymes, songs, conversations, stories in a clear way and which has repercussions on the communicative, social and educational aspects of the children. In order to carry out this research, a compilation of bibliographical information from primary and secondary sources within the educational and curricular field was applied with the aim of understanding, deepening theories, concepts, and criteria from the perspective of different pedagogues and authors with knowledge of oral-phonatory praxias and the dyslalia disorder, making it possible to understand the proposed topic. At the same time, for the development of this research, a mixed approach (qualitative and quantitative) was used, combining qualitative and quantitative methods and tools, using field, bibliographic, non-experimental, and ethnographic methods. Which allowed the study of variables when observing a social phenomenon of research with the help of techniques and instruments of data collection, making it possible to obtain information from different contexts establishing conclusions and recommendations. In addition, the research has a socio-educational impact as it will allow the design of didactic strategies to improve the children's social interaction so that they can express themselves clearly and fluently. Finally, it was concluded the importance of oral-phonatory praxias in the treatment of dyslalia in children aged 5 to 6 years because they need to exercise the muscles of the oral-phonatory organs to strengthen and coordinate the fine movements of the face, improving their pronunciation when communicating. Therefore, it is recommended to intervene practically by applying playful didactic strategies that support the development of oral language according to the needs and interests of the children.